PENGARUH FREKUENSI PEMBERIAN PAKAN YANG DITAMBAH PROBIOTIK Lactobacillus casei DENGAN DOSIS BERBEDA TERHADAP PERFORMA ITIK MAGELANG JANTAN - Miarsono Sigit; Satrio Arief Sasongko (Universitas Islam Kadiri, 2016)
This experiment was conduct to determine the effect of feed that was added probiotic Lactobacillus casei with different doses in 5-40 days male Magelang Duct performances. Research material used in this study was 120 male Magelang Ducts. Variable of this research include: feed consumtion, body weight, and feed conversion. The experiment assigned to Completely Randomized Design (RAL). When there was significant differences, then continued by Duncan’s test. The result of this study showed feed consumtion average from D0 (2433.00±19.629 g/duct), D1 (2450.03±16.504 g/duct), D2 (2479.67±31.262 g/duct). The highest feed consumption was D3 with 2485.33±32.470. The average body weight from the smallest to the highest was D1 (909.33±12.15 g/duct), D0 (911.67±7.24 g/duct), D3 (921.67±10.09 g/duct), and D2 (922.67±6.25 g/duct). The average feed consumption from the smallest to the highest was D0 (2.944±0.037), D2 (2.96±0.036), D1 (2.97±0.055) and D3 (2.97±0.046). The conclution of this research was doses of probiotic in feed and feeding frequency give the significant effect to feed consumption and body weight of ducts. The combination of this treatment give significant effect to all variables: feed consumption, body weight, and feed convertion.